(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
They arise from the uneven development of various spheres of modern human life and the contradictions that arise in people’s socio-economic, political, ideological, socio-natural and other relationships. These problems have a negative and side effect on the life of all mankind